2017
DOI: 10.7567/jjap.56.06gc01
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of krypton ion emission from a gas field ionization source with a single atom tip

Abstract: A scanning ion beam instrument equipped with a gas field ionization source (GFIS) has been commercialized, but only helium and neon are currently available as GFISs. The characteristics of krypton ion emission from a single atom tip (SAT) have not been reported yet. In this study, the characteristics of krypton ion emission were investigated by field ion microscopy. At 65 K, the krypton ion emission current reached approximately 40 pA, which is 1 order of magnitude higher than that at 130 K. As the krypton gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…The ion currents as a function of voltage (current-voltage characteristics) were also obtained at various temperatures. The krypton ion emissions were stable at the tip temperature of 65 K. Although neon and argon ion emissions have been reported (Kuo et al, 2006(Kuo et al, , 2008Livengood et al, 2011;Rahman et al, 2013;Shichi et al, 2017), it is difficult to compare our results with those reported for neon and argon ion emissions mainly because the atomic structures of the tips are different. The experimental conditions, such as emitter temperature and gas pressure, were not suitable to compare maximum possible currents.…”
Section: Introductioncontrasting
confidence: 64%
See 3 more Smart Citations
“…The ion currents as a function of voltage (current-voltage characteristics) were also obtained at various temperatures. The krypton ion emissions were stable at the tip temperature of 65 K. Although neon and argon ion emissions have been reported (Kuo et al, 2006(Kuo et al, , 2008Livengood et al, 2011;Rahman et al, 2013;Shichi et al, 2017), it is difficult to compare our results with those reported for neon and argon ion emissions mainly because the atomic structures of the tips are different. The experimental conditions, such as emitter temperature and gas pressure, were not suitable to compare maximum possible currents.…”
Section: Introductioncontrasting
confidence: 64%
“…Above the second-stage temperature of 40 K, there is a linear relationship between the tip-stem temperature and second cold-stage temperature. The tip-stem temperature is higher than the second cold-stage temperature by about 8 K (Shichi et al, 2017). The tip-stem temperature versus the second cold-stage temperature is shown in Figure 2b.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially for very light ions, such as Li, LMAIS FIBs provide nearly the same milling resolution. Improvement is possible in both cases as GFIS technology can be extended to other gases [46][47][48]. Resolution improvements should be obtainable for both technologies using better optics and optimized platforms.…”
Section: Resultsmentioning
confidence: 99%